2002
DOI: 10.1890/0012-9658(2002)083[2145:hodfro]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

How Often Do Fishes “Run on Empty”?

Abstract: We used a large data set of African, Neotropical, and North American fishes to examine the frequency with which fishes have empty stomachs (n species ϭ 254; n individuals ϭ 36 875). Mean percentage of empty stomachs was low across all fishes (16.2 Ϯ 1.2%) but varied from 0% to 79.4% among individual species. Nocturnal fishes had empty stomachs more frequently than diurnal fishes. Trophic classification was strongly associated with the percentage of empty stomachs, a pattern also revealed from an intraspecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 32 publications
6
58
0
Order By: Relevance
“…The results are in line with Huey et al (2001) and Arrington et al (2002) who showed that the average percentage of lizards and fish with empty stomachs is rather low (13 and 16%, respectively). According to Jeschke and Tollrian (2005a), herbivores also frequently reach satiation in the field.…”
Section: Discussionsupporting
confidence: 90%
“…The results are in line with Huey et al (2001) and Arrington et al (2002) who showed that the average percentage of lizards and fish with empty stomachs is rather low (13 and 16%, respectively). According to Jeschke and Tollrian (2005a), herbivores also frequently reach satiation in the field.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, any northern pike population should have some individuals representing each of the foraging sequences (i.e., searching, digesting, satiated). The feeding intervals of fishes are known to be related to the energy content, conversion efficiency, and particle size of their food (Arrington et al 2002). The consumption of high-quality food items allows individuals to rely on stored energy and forgo foraging for longer periods (Bowen 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of high-quality food items allows individuals to rely on stored energy and forgo foraging for longer periods (Bowen 1996). Empty stomachs are not necessarily related to a negative energy balance but may rather reflect the high energy content of a previously assimilated prey (Arrington et al 2002). Chapman et al (1989) suggested that the proportion of empty stomachs in northern pike is directly related to the proportion of piscivorous individuals in the population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations